Streptococcus agalactiae infection in Nile tilapia (Oreochromis niloticus) - Marcusso, Paulo Fernandes; Salvador, Rogério; Marinho-Neto, Fausto de Almeida (Revista de Ciências Agroveterinárias, 2017)
This review aims to provide greater understanding of estreptococosis in reared tilapia and thereby assist in choosing the best method of prevention and control of this disease. Streptococcus agalactiae is a cosmopolitan pathogen and the main etiologic agent of septicaemia and meningoencephalitis in teleost. Outbreaks caused by this bacteria lead to high rates of morbidity and mortality of fish, resulting in serious economic losses, especially in the cage tilapia culture that is a branch of aquaculture which produces most in Brazil. This paper presents the main estreptococosis characteristics in Nile tilapia and its prevention by using intraperitoneal vaccines. Further studies should be conducted with the intention of clarifying its pathogenesis and improving the prevention and control.